(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Dr. B.R. Ambedkar’s economic development thoughts regarding Scheduled Castes (SCs) represent a transformative framework that emphasizes social justice, political representation, and economic empowerment, rather than mere charity. His vision, rooted in the principles of liberty, equality, and fraternity, sought to dismantle the structural, caste-based inequalities that marginalized Dalits for centuries. His philosophy and, specifically, his focus on education and state-led development, remain highly relevant for the contemporary development of Scheduled Castes in India. Ambedkar linked economic reform inseparably to social reform: without annihilating caste, economic equality would remain illusory. He critiqued approaches prioritizing only property equalization (e.g., some socialist views) without addressing caste hierarchies.